FOREIGN MEDIA’S REACTION OVER POLITICAL DYNASTY IN INDONESIA - Nauvallina, Fauzia Hasna; Khristianto (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This study aims to determine the perspectives of foreign media over the issue of political dynasty issue at the last presidential election in Indonesia. This study employed a qualitative approach. The data used is news from South China Morning Post titled “Nepotism May Win Indonesia’s 2024 Election”. To analyze the political text, two theories were applied. They are appraisal theory (Martin & White, 2005) focusing on the affect as part of the attitude aspect, and the ideological square concept (van Dijk, 2006). Based on the analysis, the findings showed that the reporter felt anxious (insecurity as a part of affect) about Joko Widodo leading through political dynasties, because this could hurt Indonesia. To show his negative view, the reporter emphasizes negative points about